Longitudinal association of sarcopenia and mild cognitive impairment among older Mexican adults. Issue 6 (17th September 2021) - Salinas‐Rodríguez, Aarón; Palazuelos‐González, Rosa; Rivera‐Almaraz, Ana; Manrique‐Espinoza, Betty
Abstract: Background: Recent evidence from cross‐sectional and longitudinal studies supports the hypothesis that sarcopenia is associated with worsening cognitive function. However, primary evidence largely comes from high‐income countries, whereas in low‐ and middle‐income countries, this association has been underexplored. This study aimed to estimate the longitudinal association between sarcopenia and mild cognitive impairment in a sample of older Mexican adults. Methods: Data come from the three waves of the World Health Organization (WHO) Study on Global AGEing and Adult Health (SAGE) in Mexico (2009, 2014, 2017). Four hundred ninety‐six older adults, aged ≥50, were included. Sarcopenia was defined as having low muscle quantity and either/both slow gait speed and weak handgrip strength. Mild cognitive impairment was determined based on the recommendations of the National Institute on Aging‐Alzheimer's Association. Cognitive function was evaluated by a composite cognitive score of five different cognitive tests: immediate and delayed recall, forward and backward digit span and semantic verbal fluency. Three‐level mixed‐effects models (logistic and linear) were used to estimate the longitudinal associations between sarcopenia, mild cognitive impairment and cognitive function. Results: The prevalence of mild cognitive impairment (8.9%, 12.9%, 16.0%) and sarcopenia (10.5%, 20.7%, 23.3%) showed a significant temporal increase for Waves 1, 2 and 3 ( P ‐value < 0.01, respectively). The presence of sarcopenia was significantly associated with mild cognitive impairment (OR = 1.74; CI95% 1.02, 2.96; P = 0.04) and worse cognitive function (β = −0.57; CI95% ‐0.93, −0.21; P < 0.01). We observed significant associations between sarcopenia and immediate verbal recall (β = −0.14; CI95% −0.28, −0.01; P = 0.04), delayed verbal recall (β = −0.12; CI95% −0.23, −0.01; P = 0.03) and semantic verbal fluency (β = −0.17; CI95% −0.28, −0.05; P = 0.01). The prevalence of mild cognitive impairment increased at an annual rate of 0.8% for non‐sarcopenic older adults, but nearly 1.5% for sarcopenic adults. Conclusions: Significant longitudinal associations were observed between sarcopenia, mild cognitive impairment and cognitive function among older Mexican adults. Public health strategies, including policy research and clinical interventions, must be implemented in low‐ and middle‐income countries in order to reduce or delay the onset of sarcopenia and thus improve population‐level cognitive health among older adults.